Max Weber and the Problem of a ‘Successful Peace’ - Bruhns, Hinnerk (Simmel Studies, 2018)
“How can we think of peace? And when?”, Max Weber asks in a letter to Ferdinand Tönnies, in 14 October 1914. This article focuses on the concept of “successful” peace, the decisive concept for Weber’s ideas about the “way out of the war” that the author refined between 1914–1918 in his speeches, texts and letters. For Weber, a successful peace depended not only on the foreign policy dimension but even more on important inner reforms and a fundamental reorganisation of the German Reich. Analysing Weber’s “ideas of 1918” – radically opposed to the well-known “ideas of 1914” – this paper focuses on three aspects: (1) nation and state citizens (2) Prussia, (3) German tradition, history and political culture, before outlining, at the end, Weber’s ideas about the European post-war order.